2002
DOI: 10.1038/nsb873
|View full text |Cite
|
Sign up to set email alerts
|

Sculpting of the spliceosomal branch site recognition motif by a conserved pseudouridine

Abstract: Pairing of a consensus sequence of the precursor (pre)-mRNA intron with a short region of the U2 small nuclear (sn)RNA during assembly of the eukaryotic spliceosome results in formation of a complementary helix of seven base pairs with a single unpaired adenosine residue. The 2' OH of this adenosine, called the branch site, brings about nucleophilic attack at the pre-mRNA 5' splice site in the first step of splicing. Another feature of this pairing is the phylogenetic conservation of a pseudouridine (psi) resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
124
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(135 citation statements)
references
References 46 publications
11
124
0
Order By: Relevance
“…Yang et al used a genetic synthetic lethal screen to demonstrate that Ψ35, when coupled with a U2 point mutation at position 40, is required for pre-mRNA splicing in S. cerevisiae . This result is consistent with an NMR study showing that, when paired with the pre-mRNA branch site, Ψ35 is favored over uridine for maintaining the bulge of the branch point nucleotide adenosine for the nucleophilic attack in the first step of splicing (Newby and Greenbaum, 2002). However, it is worth mentioning a recent work by the Kielkopf group on the crystal structure of the pseudouridylated (Ψ35) U2 branch site recognition region duplexed with the premRNA branch site (Lin and Kielkopf, 2008).…”
Section: Pseudouridylation Of U2 Is Required For Snrnp Assemblysupporting
confidence: 88%
“…Yang et al used a genetic synthetic lethal screen to demonstrate that Ψ35, when coupled with a U2 point mutation at position 40, is required for pre-mRNA splicing in S. cerevisiae . This result is consistent with an NMR study showing that, when paired with the pre-mRNA branch site, Ψ35 is favored over uridine for maintaining the bulge of the branch point nucleotide adenosine for the nucleophilic attack in the first step of splicing (Newby and Greenbaum, 2002). However, it is worth mentioning a recent work by the Kielkopf group on the crystal structure of the pseudouridylated (Ψ35) U2 branch site recognition region duplexed with the premRNA branch site (Lin and Kielkopf, 2008).…”
Section: Pseudouridylation Of U2 Is Required For Snrnp Assemblysupporting
confidence: 88%
“…[10,33] For example, in yeast, where the two systems are most closely related, the spliceosomal branch-A is not flanked by GU-wobbles, a feature that is highly conserved in group IIB introns. [10] Instead, a conserved spliceosomal seven nucleotide sequence [34] together with a pseudouridine opposite to the branch adenosine are likely to be responsible for the single bulgedout branch A, [35] which must be unpaired for successful splicing. In the group II intron ai5γ on the other hand, a base paired branch A does not completely abolish branching.…”
Section: Discussionmentioning
confidence: 99%
“…[36,37] NMR structural analyses have shown that this Ψ is responsible for an extrahelical positioning of the branch adenosine in the isolated branch helix. [35,38] Although no Ψ has been identified in group II introns to date, the relationship with the spliceosome makes a bulged-out adenosine in context of the whole group II intron also tempting to propose. However, in the light of the many differences between the two systems and the here presented solution structure of an active D6 construct, the occurrence of a helically stacked branch adenosine should be considered more closely.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudouridine is known to affect the structure of tRNAs, affecting base-stacking (5) in the anticodon loop, and when it appears in stems or the anticodon, it strengthens base-pairing (6,(32)(33)(34). When modeled with RNA oligomers, the presence of ⌿ in U2 small nuclear RNA causes a change in the structure of the lariat branch point of pre-messenger RNA (35,36). A functional requirement for ⌿ in U2 small nuclear RNA has also been shown in reconstitution of splicing systems (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%